2021
DOI: 10.1002/chem.202004527
|View full text |Cite
|
Sign up to set email alerts
|

A pH‐Induced Reversible Conformational Switch Able to Control the Photocurrent Efficiency in a Peptide Supramolecular System

Abstract: External stimuli are potent tools that Nature uses to control protein function and activity. For instance, during viral entry and exit, pH variations are known to trigger large protein conformational changes. In Nature, also the electron transfer (ET) properties of ET proteins are influenced by pH‐induced conformational changes. In this work, a pH‐controlled, reversible 310‐helix to α‐helix conversion (from acidic to highly basic pH values and vice versa) of a peptide supramolecular system built on a gold surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…The presence of four Lys residues makes the peptide pH-sensitive [2,4]. We previously reported that Lys-containing trichogin analogs were able to switch their conformation reversibly between fully-developed α-helix and 310-helix in response to pH variation.…”
Section: Fig 2 CD Spectra Of T-tric-a As a Function Of Increasing Pep...mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of four Lys residues makes the peptide pH-sensitive [2,4]. We previously reported that Lys-containing trichogin analogs were able to switch their conformation reversibly between fully-developed α-helix and 310-helix in response to pH variation.…”
Section: Fig 2 CD Spectra Of T-tric-a As a Function Of Increasing Pep...mentioning
confidence: 99%
“…We also describe the effect on ET-through-peptide of a pH-controlled, reversible 310to α-helix conversion, with a focus on the effect of the pH-induced conformational change on photocurrent efficiency [2]. The biomolecular devices were characterized by electrochemical and spectroscopic techniques, and were able to generate current under illumination, with an efficiency that is the highest recorded so far with biomolecular systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides are often able to provide a selective response to external stimuli, such as the presence of a specific analyte [9][10][11][12][13][14][15][16][17]. One of the most common reactions of peptides to an external stimulus is to undergo a conformational change that might be reversible [18][19][20]. The activation can be triggered by a non-covalent interaction between the analyte and the peptide binding site or induced by temperature or pressure variation or light [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the photocurrent polarity switching strategy can be realized by tuning incident light wavelengths, applied voltage, , pH of the electrolyte, surface modification on semiconductors, ,, and so on. Among them, adjusting the applied voltage is a simple, portable way to reverse photocurrent polarity without extra cumbersome operating procedures.…”
mentioning
confidence: 99%